Digitalisasi Monitoring dan Penugasan Operasional Lapangan Menggunakan Metode Waterfall: Studi Kasus PT Lintas Data Prima - Lulu Angelita; Alfino Kurniawan; Hadhyan Sultan Aljavier (Riset Sinergi Indonesia (RISINDO), 2026)
PT Lintas Data Prima is a company providing internet and information technology services, where the efficiency of operational monitoring and team assignment is the main key to maintaining service quality. However, monitoring and task distribution processes that are still manual or conventional often trigger coordination challenges, delays in handling disruptions, and difficulties in tracking field team performance in real-time. This study aims to design and build a website-based digitalized monitoring and assignment system for field operations to optimize work efficiency and management control. The method used in this system development is the Waterfall method, which is applied systematically starting from requirements analysis, system design, coding, testing, to implementation. The result of this research is a digital information system application that successfully accelerates the task distribution process, presents transparent visualization of assignment status, and facilitates the management in performance monitoring of field technicians at PT Lintas Data Prima.